Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,369 questions

17,804 answers

1,438 comments

36,292 users

solve the system by the method using elimination 6x+3y=-12 and 6x+2y=-4

0 votes

solve the equation

asked Dec 4, 2013 in ALGEBRA 1 by payton Apprentice

1 Answer

0 votes

Elimination method

Given equaions are 6x+3y = -12 -------> (1)

6x+2y = -4 --------> (2)

To eliminate the x , subtract equation (1) from (2).

6x+2y = -4

6x+3y = -12

(-) (-)    (+)

_________

-y = 8

Muliply to each side by negitive one.

y = -8

Substiue the y value in (1).

6x+3*-8 = -12

6x-24 = -12

Add 24 to each side.

6x-24+24 = -12+24

6x = 12

Divide to each side by 6.

6x/6 = 12/6

x = 2

Soluion x = 2, y = -8.

answered Dec 4, 2013 by william Mentor

Related questions

...